Mutations of the Transcriptional Corepressor ZMYM2 Cause Syndromic Urinary Tract Malformations. - Connaughton, Dervla M; Dai, Rufeng; Owen, Danielle J; Marquez, Jonathan; Mann, Nina; GrAHm-Paquin, Adda L; Nakayama, Makiko; Coyaud, Etienne; Laurent, Estelle M N; St-Germain, Jonathan R; Blok, Lot Snijders; Vino, Arianna; et al. (Am J Hum Genet, 2020)
Congenital anomalies of the kidney and urinary tract (CAKUT) constitute one of the most frequent birth defects and represent the most common cause of chronic kidney disease in the first three decades of life. Despite the discovery of dozens of monogenic causes of CAKUT, most pathogenic pathways remain elusive. We performed whole-exome sequencing (WES) in 551 individuals with CAKUT and identified a heterozygous de novo stop-gain variant in ZMYM2 in two different families with CAKUT. Through collaboration, we identified in total 14 different heterozygous loss-of-function mutations in ZMYM2 in 15 unrelated families. Most mutations occurred de novo, indicating possible interference with reproductive function. Human disease features are replicated in X. tropicalis larvae with morpholino knockdowns, in which expression of truncated ZMYM2 proteins, based on individual mutations, failed to rescue renal and craniofacial defects. Moreover, heterozygous Zmym2-deficient mice recapitulated features of CAKUT with high penetrance. The ZMYM2 protein is a component of a transcriptional corepressor complex recently linked to the silencing of developmentally regulated endogenous retrovirus elements. Using protein-protein interaction assays, we show that ZMYM2 interacts with additional epigenetic silencing complexes, as well as confirming that it binds to FOXP1, a transcription factor that has also been linked to CAKUT. In summary, our findings establish that loss-of-function mutations of ZMYM2, and potentially that of other proteins in its interactome, as causes of human CAKUT, offering new routes for studying the pathogenesis of the disorder.
Keywords: Amphibian Proteins; Animals; Case-Control Studies; Child; Child, Preschool; DNA-Binding Proteins; Epigenesis, Genetic; Family; Female; Forkhead Transcription Factors; Heterozygote; Humans; Infant; Larva; Male; Mice; Mice, Knockout; Morpholinos; Mutation; Pedigree; Protein Binding; Repressor Proteins; Transcription Factors; Urinary Tract; Urogenital Abnormalities; Whole Exome Sequencing; Xenopus

Whole exome sequencing identified ATP6V1C2 as a novel candidate gene for recessive distal renal tubular acidosis. - Jobst-Schwan, Tilman; Klämbt, Verena; Tarsio, Maureen; Heneghan, John F; Majmundar, Amar J; Shril, Shirlee; Buerger, Florian; Ottlewski, Isabel; Shmukler, Boris E; Topaloglu, Rezan; Hashmi, Seema; Hafeez, Farkhanda; et al. (Kidney Int, 2020)
Distal renal tubular acidosis is a rare renal tubular disorder characterized by hyperchloremic metabolic acidosis and impaired urinary acidification. Mutations in three genes (ATP6V0A4, ATP6V1B1 and SLC4A1) constitute a monogenic causation in 58-70% of familial cases of distal renal tubular acidosis. Recently, mutations in FOXI1 have been identified as an additional cause. Therefore, we hypothesized that further monogenic causes of distal renal tubular acidosis remain to be discovered. Panel sequencing and/or whole exome sequencing was performed in a cohort of 17 families with 19 affected individuals with pediatric onset distal renal tubular acidosis. A causative mutation was detected in one of the three "classical" known distal renal tubular acidosis genes in 10 of 17 families. The seven unsolved families were then subjected to candidate whole exome sequencing analysis. Potential disease causing mutations in three genes were detected: ATP6V1C2, which encodes another kidney specific subunit of the V-type proton ATPase (1 family); WDR72 (2 families), previously implicated in V-ATPase trafficking in cells; and SLC4A2 (1 family), a paralog of the known distal renal tubular acidosis gene SLC4A1. Two of these mutations were assessed for deleteriousness through functional studies. Yeast growth assays for ATP6V1C2 revealed loss-of-function for the patient mutation, strongly supporting ATP6V1C2 as a novel distal renal tubular acidosis gene. Thus, we provided a molecular diagnosis in a known distal renal tubular acidosis gene in 10 of 17 families (59%) with this disease, identified mutations in ATP6V1C2 as a novel human candidate gene, and provided further evidence for phenotypic expansion in WDR72 mutations from amelogenesis imperfecta to distal renal tubular acidosis.

Whole-Exome Sequencing Enables a Precision Medicine Approach for Kidney Transplant Recipients. - Mann, Nina; Braun, Daniela A; Amann, Kassaundra; Tan, Weizhen; Shril, Shirlee; Connaughton, Dervla M; Nakayama, Makiko; Schneider, Ronen; Kitzler, Thomas M; van der Ven, Amelie T; Chen, Jing; Ityel, Hadas; et al. (J Am Soc Nephrol, 2019)
BACKGROUND: Whole-exome sequencing (WES) finds a CKD-related mutation in approximately 20% of patients presenting with CKD before 25 years of age. Although provision of a molecular diagnosis could have important implications for clinical management, evidence is lacking on the diagnostic yield and clinical utility of WES for pediatric renal transplant recipients. METHODS: To determine the diagnostic yield of WES in pediatric kidney transplant recipients, we recruited 104 patients who had received a transplant at Boston Children's Hospital from 2007 through 2017, performed WES, and analyzed results for likely deleterious variants in approximately 400 genes known to cause CKD. RESULTS: By WES, we identified a genetic cause of CKD in 34 out of 104 (32.7%) transplant recipients. The likelihood of detecting a molecular genetic diagnosis was highest for patients with urinary stone disease (three out of three individuals), followed by renal cystic ciliopathies (seven out of nine individuals), steroid-resistant nephrotic syndrome (nine out of 21 individuals), congenital anomalies of the kidney and urinary tract (ten out of 55 individuals), and chronic glomerulonephritis (one out of seven individuals). WES also yielded a molecular diagnosis for four out of nine individuals with ESRD of unknown etiology. The WES-related molecular genetic diagnosis had implications for clinical care for five patients. CONCLUSIONS: Nearly one third of pediatric renal transplant recipients had a genetic cause of their kidney disease identified by WES. Knowledge of this genetic information can help guide management of both transplant patients and potential living related donors.
Keywords: Adolescent; Boston; Child; Child, Preschool; Cohort Studies; Female; Genetic Predisposition to Disease; Genetic Testing; Graft Rejection; Graft Survival; Hospitals, Pediatric; Humans; Kidney Transplantation; Male; Precision Medicine; Prognosis; Renal Insufficiency, Chronic; Retrospective Studies; Risk Assessment; Severity of Illness Index; Survival Analysis; Transplant Recipients; Treatment Outcome; Whole Exome Sequencing

Whole exome sequencing frequently detects a monogenic cause in early onset nephrolithiasis and nephrocalcinosis. - Daga, Ankana; Majmundar, Amar J; Braun, Daniela A; Gee, Heon Yung; Lawson, Jennifer A; Shril, Shirlee; Jobst-Schwan, Tilman; Vivante, Asaf; Schapiro, David; Tan, Weizhen; Warejko, Jillian K; Widmeier, Eugen; et al. (Kidney Int, 2018)
The incidence of nephrolithiasis continues to rise. Previously, we showed that a monogenic cause could be detected in 11.4% of individuals with adult-onset nephrolithiasis or nephrocalcinosis and in 16.7-20.8% of individuals with onset before 18 years of age, using gene panel sequencing of 30 genes known to cause nephrolithiasis/nephrocalcinosis. To overcome the limitations of panel sequencing, we utilized whole exome sequencing in 51 families, who presented before age 25 years with at least one renal stone or with a renal ultrasound finding of nephrocalcinosis to identify the underlying molecular genetic cause of disease. In 15 of 51 families, we detected a monogenic causative mutation by whole exome sequencing. A mutation in seven recessive genes (AGXT, ATP6V1B1, CLDN16, CLDN19, GRHPR, SLC3A1, SLC12A1), in one dominant gene (SLC9A3R1), and in one gene (SLC34A1) with both recessive and dominant inheritance was detected. Seven of the 19 different mutations were not previously described as disease-causing. In one family, a causative mutation in one of 117 genes that may represent phenocopies of nephrolithiasis-causing genes was detected. In nine of 15 families, the genetic diagnosis may have specific implications for stone management and prevention. Several factors that correlated with the higher detection rate in our cohort were younger age at onset of nephrolithiasis/nephrocalcinosis, presence of multiple affected members in a family, and presence of consanguinity. Thus, we established whole exome sequencing as an efficient approach toward a molecular genetic diagnosis in individuals with nephrolithiasis/nephrocalcinosis who manifest before age 25 years.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Disease Progression; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Heredity; Humans; Infant; Male; Mutation; Nephrocalcinosis; Nephrolithiasis; Pedigree; Phenotype; Predictive Value of Tests; Prognosis; Risk Factors; Tomography, X-Ray Computed; Ultrasonography; Whole Exome Sequencing; Young Adult

Whole Exome Sequencing Reveals a Monogenic Cause of Disease in ≈43% of 35 Families With Midaortic Syndrome. - Warejko, Jillian K; Schueler, Markus; Vivante, Asaf; Tan, Weizhen; Daga, Ankana; Lawson, Jennifer A; Braun, Daniela A; Shril, Shirlee; Amann, Kassaundra; Somers, Michael J G; Rodig, Nancy M; Baum, Michelle A; et al. (Hypertension, 2018)
Midaortic syndrome (MAS) is a rare cause of severe childhood hypertension characterized by narrowing of the abdominal aorta in children and is associated with extensive vascular disease. It may occur as part of a genetic syndrome, such as neurofibromatosis, or as consequence of a pathological inflammatory disease. However, most cases are considered idiopathic. We hypothesized that in a high percentage of these patients, a monogenic cause of disease may be detected by evaluating whole exome sequencing data for mutations in 1 of 38 candidate genes previously described to cause vasculopathy. We studied a cohort of 36 individuals from 35 different families with MAS by exome sequencing. In 15 of 35 families (42.9%), we detected likely causal dominant mutations. In 15 of 35 (42.9%) families with MAS, whole exome sequencing revealed a mutation in one of the genes previously associated with vascular disease (, , , , and ). Ten of the 15 mutations have not previously been reported. This is the first report of , , or mutations in individuals with MAS. Mutations were detected in (6/15 families), (4/15 families), (3/15 families), and one family each for and Eight individuals had syndromic disease and 7 individuals had isolated MAS. Whole exome sequencing can provide conclusive molecular genetic diagnosis in a high fraction of individuals with syndromic or isolated MAS. Establishing an etiologic diagnosis may reveal genotype/phenotype correlations for MAS in the future and should, therefore, be performed routinely in MAS.
Keywords: Adolescent; Aorta, Abdominal; Aortic Valve Stenosis; Child; Child, Preschool; Cohort Studies; Female; Genetic Association Studies; Humans; Hypertension; Jagged-1 Protein; Male; Mutation; Neurofibromatoses; Neurofibromin 1; Pedigree; Syndrome; United States; Whole Exome Sequencing

Whole-Exome Sequencing Identifies Causative Mutations in Families with Congenital Anomalies of the Kidney and Urinary Tract. - van der Ven, Amelie T; Connaughton, Dervla M; Ityel, Hadas; Mann, Nina; Nakayama, Makiko; Chen, Jing; Vivante, Asaf; Hwang, Daw-Yang; Schulz, Julian; Braun, Daniela A; Schmidt, Johanna Magdalena; Schapiro, David; et al. (J Am Soc Nephrol, 2018)
BACKGROUND: Congenital anomalies of the kidney and urinary tract (CAKUT) are the most prevalent cause of kidney disease in the first three decades of life. Previous gene panel studies showed monogenic causation in up to 12% of patients with CAKUT. METHODS: We applied whole-exome sequencing to analyze the genotypes of individuals from 232 families with CAKUT, evaluating for mutations in single genes known to cause human CAKUT and genes known to cause CAKUT in mice. In consanguineous or multiplex families, we additionally performed a search for novel monogenic causes of CAKUT. RESULTS: In 29 families (13%), we detected a causative mutation in a known gene for isolated or syndromic CAKUT that sufficiently explained the patient's CAKUT phenotype. In three families (1%), we detected a mutation in a gene reported to cause a phenocopy of CAKUT. In 15 of 155 families with isolated CAKUT, we detected deleterious mutations in syndromic CAKUT genes. Our additional search for novel monogenic causes of CAKUT in consanguineous and multiplex families revealed a potential single, novel monogenic CAKUT gene in 19 of 232 families (8%). CONCLUSIONS: We identified monogenic mutations in a known human CAKUT gene or CAKUT phenocopy gene as the cause of disease in 14% of the CAKUT families in this study. Whole-exome sequencing provides an etiologic diagnosis in a high fraction of patients with CAKUT and will provide a new basis for the mechanistic understanding of CAKUT.